2020
DOI: 10.1136/jnnp-2019-322588
|View full text |Cite
|
Sign up to set email alerts
|

Serum neuronal exosomes predict and differentiate Parkinson’s disease from atypical parkinsonism

Abstract: ObjectiveParkinson’s disease is characterised neuropathologically by α-synuclein aggregation. Currently, there is no blood test to predict the underlying pathology or distinguish Parkinson’s from atypical parkinsonian syndromes. We assessed the clinical utility of serum neuronal exosomes as biomarkers across the spectrum of Parkinson’s disease, multiple system atrophy and other proteinopathies.MethodsWe performed a cross-sectional study of 664 serum samples from the Oxford, Kiel and Brescia cohorts consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
245
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(265 citation statements)
references
References 47 publications
17
245
3
Order By: Relevance
“…Numerous studies have confirmed that exosomal miRNAs may be used as biomarkers for early cancer detection and monitoring compared with traditional blood-based cancer markers (37)(38)(39). The present study also demonstrated a significant reduction in exosomal miR-1273a in the plasma of patients who were not sensitive to platinum-based chemotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…Numerous studies have confirmed that exosomal miRNAs may be used as biomarkers for early cancer detection and monitoring compared with traditional blood-based cancer markers (37)(38)(39). The present study also demonstrated a significant reduction in exosomal miR-1273a in the plasma of patients who were not sensitive to platinum-based chemotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…26 The combination of multiple markers improved the diagnostic accuracy of neuronal-derived exosomes as shown by a recent work on quantification of both αSyn and clusterin differentiating PD from other proteinopathies and from MSA with high accuracy (AUC 0.98 and 0.94, respectively). 27 This analysis of multiple immune surface markers of circulating EVs in PD and AP shows a high diagnostic performance, likely due to the advantage of simultaneously profiling several EV subpopulations. First of all, we demonstrated that plasma EV concentration was higher in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…EV-associated α-Syn has been detected in saliva, plasma, CSF, and serum from PD patients. Although sometimes its levels were found controversial in different reports, it is possible to envisage the use of EV-α-Syn as a valid PD biomarker in the near future [161][162][163][164][165][166][167][168][169][170][171].…”
Section: Pd Signature Markers In Evsmentioning
confidence: 99%
“…Also, the presence of DJ-1 inside EVs has been analyzed in urine and plasma samples from PD patients. EV-DJ-1 levels are higher in PD subjects compared to controls, even if further studies need to confirm its validity as a novel PD biomarker [164,175,176]. Another interesting finding about EV-based biomarkers can be ascribed to the presence of cellular prion protein (PrPC) in EVs derived from PD patient plasma samples [177].…”
Section: Pd Signature Markers In Evsmentioning
confidence: 99%